Energy efficiency in FKE's offices and lecturer's room - Hairil Aswad Jamaludin, 1988-, author; Mohammad Yusri Hassan, supervisor; Fakulti Kejuruteraan Elektrik (2012)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2012